(untitled) (Research, Society and Development, 2024)
Objective: to analyze the effectiveness of the Roux-en-Y Gastric Bypass and Gastric Sleeve techniques, currently the main bariatric surgery techniques, and analyze the difference in results between them. Both techniques are recommended for the treatment of Obesity Grade 3 (BMI ≥ 40.0 kg/m²), Grade 2 (BMI = 35-39.9 kg/m²) with comorbidities and Grade 1 (BMI = 30-34.9 kg/m²) with comorbidities considered "serious". Methodology: the research was characterized as a descriptive cross-sectional study. Data collection was carried out in May 2023 at a bariatric clinic in Western Paraná. The main data collected were: Sex, Age, BMI (pre-surgery and 3 years after the procedure) and comorbidities, and 50 patients participated in the sample. The data were organized in a Microsoft Excel spreadsheet for descriptive analysis. Result: from the data collected, the impact of both surgical techniques on BMI was evident, causing a significant reduction in it. It is noted, analyzing the tables, a predominance between one of the sexes in carrying out the surgery, a greater reduction in BMI through one of the techniques and the possibility of verifying which age group was most subjected to surgery. Conclusion: it is possible to verify, through the results, that both techniques provide a reduction in BMI, which guarantees an improvement in the patient’s quality of life, highlighting the Bypass technique, which proved to be more effective in reducing, and it is also verified that females were the ones who performed this surgery the most.